2017
DOI: 10.3813/aaa.919046
|View full text |Cite
|
Sign up to set email alerts
|

Wheel of Concert Hall Acoustics

Abstract: SummaryMore than ah undred years of research on concert hall acoustics has provided an extensive list of attributes to describe and evaluate the perceptual aspects of sound in concert halls. This brief overviewdiscusses the current knowledge, and presents a"wheel of concert hall acoustics" in which the main aspects are gathered together with the descriptive attributes that are commonly encountered in the research literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…For such measurement, a crucial step is to define, or possibly elicit the attributes that are used to quantify the sensory experience. For the evaluation of audio, several sets of attributes and recommendations for developing attributes have been suggested [71,57]. It is assumed that the sensory strengths of each attribute in stimuli or the relation of the sensory strengths between stimuli can be measured using psychometric techniques.…”
Section: Experimental Methods For Perceptual Evaluation Of Room Acous...mentioning
confidence: 99%
“…For such measurement, a crucial step is to define, or possibly elicit the attributes that are used to quantify the sensory experience. For the evaluation of audio, several sets of attributes and recommendations for developing attributes have been suggested [71,57]. It is assumed that the sensory strengths of each attribute in stimuli or the relation of the sensory strengths between stimuli can be measured using psychometric techniques.…”
Section: Experimental Methods For Perceptual Evaluation Of Room Acous...mentioning
confidence: 99%
“…In studies of the perception of room acoustic properties, three aspects have consistently been shown to be constitutive in determining the acoustic impact of rooms, such as musical performance spaces-see Kuusinen and Lokki (2017) or Weinzierl and Vorl€ ander (2015) for an overview. These are…”
Section: B Room Acoustical Qualitiesmentioning
confidence: 99%
“…As a summary of their own and other work, authors of the same group suggested a "wheel of concert hall acoustics", including eight main categories and 33 items to visualize the main perceptual aspects of concert halls with unamplified musical instrument sounds (Kuusinen and Lokki 2017). The wheel format, which has a longer tradition in the domain of food quality and sensory evaluation (compare Noble et al 1987) is a structured and hierarchical form to present a lexicon of different sensory characteristics.…”
Section: Linguistic Inventories As a Basis For Psychological Measurin...mentioning
confidence: 99%